FINANCIAL LITERACY, FINANCIAL TECHNOLOGY AND MSME PERFORMANCE IN BUNGO DISTRICT: THE ROLE OF MANAGEMENT MEDIATION FINANCE - Sophia, Ade; Putra, Wirmie Eka; Hernando, Riski (Politeknik Negeri Ambon, 2025)
Introduction: This research examined the effects of financial literacy and financial technology on the performance of MSMEs, with financial management as a mediating variable, in Bungo Regency. Method: This study applied a quantitative research method. Primary data were collected using an online and offline questionnaire, completed by MSMEs in Bungo Regency. The sample size was 391 MSMEs. The study employed Partial Least Squares (PLS)-SEM using SmartPLS 4.1. Results: Financial Literacy gives no effects to the Performance of MSMEs in Bungo Regency as seen by the t-statistic value in 1.804 > 1.96 and also the p-value of 0.071 < sig 0.005,Financial Technology has an effect on the MSMEs performance in Bungo Regency as seen by the t-statistic value of 3.784 > 1.96 and also the p value 0.000 < sig 0.005, Financial Literacy gives an influence toward Financial Management as evidenced by the t-statistic value of 4.766 > 1.96 and also p value of 0.000 < sig 0.005,Financial Technology gives such a n impact toward Financial Management as seen by the t-statistic value of 4.766 > 1.96 and the p-value of 0.000 < sig 0.005, Financial Management gives an influence toward Performance of MSMEs in Bungo Regency as evidenced by the t-statistic value of 6.363 > 1.96 and the p value of value of 0.000 < sig 0.005, Financial literacy gives such an influence tward MSMEs performance in Bungo Regency through financial management as seen by the t-statistic value in 3.634 > 1.96 and also ,the p value of value of 0.000 < sig 0.005,Financial Technology gives such an influence toward performance of MSMEs in Bungo Regency through financial management as evidenced by the t-statistic value of 3,905 > 1.96 and also the p-value value of 0.000 < sig 0.005. Keywords: Financial Literacy, Financial Technology, Financial Management, MSMEs Performance